Development of Indonesian language book using glasser model - Syamsuyurnita Syamsuyurnita; Dewi Kesuma Nasution (English, 2017)
This study aims to describe the process of developing teaching materials by using Glasser model in the Indonesian language course in FKIP UMSU. The sample of the research is 34-second semester A morning students in the Study Program of Language and Literature of Indonesia, Faculty of Teacher Training and Education, University of Muhammadiyah, Sumatera Utara. The questionnaire instrument was used to determine the student's response and activeness to the developed teaching material, the observation sheet used to know the condition of the students in the learning process, and the validation sheet instrument used for the development of teaching materials based on SAP using Glasser model. The result of descriptive research on student's response shows that 100% of students were happy about the teaching materials of Bahasa Indonesia (Teaching Materials, Guided Exercises and Lecture Strategies) and 91.66% of students think that the teaching materials are new to them. After using the teaching materials developed by the researcher and following the teaching and learning activities, students (100%) are interested in following the next lesson, the readability of the language of the learning material is easy to understand (91.66%) and the guidance given by the lecturer is clear (100%). While the self-employed activity is fun for students (91.66%). Students activity in learning activities was shown by their involvement in problem solving, his involvement in carrying out learning tasks, assessing his ability, digging and developing his own knowledge. Based on the validation sheet on the test of learning result 1 obtained information that from the 3 learning objectives formulated in SAP I and SAP II there is 1 learning objectives that have not yet completed. Based on the results of descriptive analysis of the test results of learning 2 it was obtained that the 3 learning objectives formulated in SAP III and SAP IV was finished learning objective.